Answer:
Length of Shorter leg = 27 feet
Length of Longer leg = 36 feet
Length of Hypotenuse = 45 feet
Step-by-step explanation:
Given:
Let,
Length of Shorter leg = x,
According to the given condition we have
∴ Length of Longer leg = x + 9 feet
∴ Length of Hypotenuse = 2x - 9 feet
To Find:
Length of Shorter leg = ?
Solution:
Now In Right Angle Triangle, By Pythagoras theorem we have
![(\textrm{Hypotenuse})^{2} = (\textrm{Shorter leg})^{2}+(\textrm{Longer leg})^{2}](https://tex.z-dn.net/?f=%28%5Ctextrm%7BHypotenuse%7D%29%5E%7B2%7D%20%3D%20%28%5Ctextrm%7BShorter%20leg%7D%29%5E%7B2%7D%2B%28%5Ctextrm%7BLonger%20leg%7D%29%5E%7B2%7D)
substituting the given values we get
![(2x-9)^{2} = (x)^{2}+(x+9)^{2}\\](https://tex.z-dn.net/?f=%282x-9%29%5E%7B2%7D%20%3D%20%28x%29%5E%7B2%7D%2B%28x%2B9%29%5E%7B2%7D%5C%5C)
By using Identity (A ± B)² = A² ± 2AB +B² we get
![4x^{2} -36x+81=x^{2} +(x^{2} +18x+81)\\\\4x^{2} -2x^{2} -36x-18x=81-81\\\\2x^{2} -54x=0\\2x(x-27)=0\\2x=0 or x-27=0\\\therefore x\ cannot\ be \ zero\\\therefore x = 27 \feet](https://tex.z-dn.net/?f=4x%5E%7B2%7D%20-36x%2B81%3Dx%5E%7B2%7D%20%2B%28x%5E%7B2%7D%20%2B18x%2B81%29%5C%5C%5C%5C4x%5E%7B2%7D%20-2x%5E%7B2%7D%20-36x-18x%3D81-81%5C%5C%5C%5C2x%5E%7B2%7D%20-54x%3D0%5C%5C2x%28x-27%29%3D0%5C%5C2x%3D0%20or%20x-27%3D0%5C%5C%5Ctherefore%20x%5C%20cannot%5C%20be%20%5C%20zero%5C%5C%5Ctherefore%20x%20%3D%2027%20%5Cfeet)
Substituting x=27 we get
∴ Length of Longer leg = x + 9 =27 +9 = 36 feet
∴ Length of Hypotenuse = 2x - 9 = 2×27 -9 = 45 feet